Impaired maturation of serotonergic function in the dentate gyrus associated with epilepsy - Kate Elizabeth Gilling; Frank Oltmanns; Joachim Behr (Neurobiology of Disease, 2013)
Temporal lobe epilepsy is believed to develop after an initial precipitating injury, usually suffered in childhood or adolescence, and aspects include impaired maturation of the hippocampus, and specifically the dentate gyrus. The dentate gyrus receives a major serotonergic input from the brainstem raphe nuclei, and the serotonergic system may regulate neurogenesis in the developing and mature hippocampus. The aim of this work was to investigate changes which may be associated with abnormal functioning of the serotonergic system in the pilocarpine model of epilepsy, where spontaneous seizures are induced by administration of pilocarpine at 6 weeks of age. Application of serotonin (100 μM) led to a transient hyperpolarization of the resting membrane potential and decrease of the input resistance mediated by the 5-HT1A receptor that was similar between control and pilocarpine-treated animals and unaffected by the age of the animal. In the younger, but not in older control animals, serotonin led to a 5-HT2 receptor-mediated long-term depression of evoked postsynaptic currents, a normal functional shift in the early adulthood of the Wistar rat. In pilocarpine-treated animals, this long-term depression persisted in older animals, indicating impaired maturation of the dentate gyrus. These data may indicate 5-HT2 receptor function to be affected by the pathology of temporal lobe epilepsy.